\(e^+ e^- → hZ\) Collision in Randall-Sundrum Model - Giang, Bui Thi Ha; Thuy, Dao Thi Le (Communications in Physics, 2016)
We study the production of Higgs and Z bosons which has been proposed as an option of \(e^+e^-\) collision at the ILC, CLIC with the polarization of the electron and positron beams in Randall-Sundrum model (RSM). The differential cross-sections are presented and numerical evaluation is given. Based on the results, we show that the advantageous direction to collect Higgs is perpendicular to the direction of the initial \(e^-\) beam. With the high integrated luminosity and at the high degree of polarization, the reaction can give observable cross-sections in future accelerators (ILC, CLIC).